Exogenous gibberellins induce wheat spike development under short days only in the presence of VERNALIZATION1. - Pearce, Stephen (2013)
The activation of the meristem identity gene VERNALIZATION1 (VRN1) is a critical regulatory point in wheat (Triticum spp.) flowering. In photoperiod-sensitive wheat varieties, VRN1 is expressed only under long days (LDs), but mutants carrying deletions in a regulatory element in its promoter show VRN1 transcription and early spike development under short days (SDs). However, complete spike development is delayed until plants are transferred to LDs, indicating the existence of an additional regulatory mechanism dependent on LDs. We show here that exogenous gibberellin (GA) application accelerates spike development under SDs, but only in wheat lines expressing VRN1. The simultaneous presence of GA and VRN1 results in the up-regulation of the floral meristem identity genes SUPPRESSOR OF OVEREXPRESSION OF CONSTANS1-1 and LEAFY, whereas inhibition of GA biosynthesis with paclobutrazol precludes the LD induction of these two genes. The inductive role of GA on wheat flowering is further supported by the up-regulation of GA biosynthetic genes in the apices of plants transferred from SDs to LDs and in photoperiod-insensitive and transgenic wheat plants with increased FLOWERING LOCUS T transcription under SDs. The up-regulation of GA biosynthetic genes was not observed in the leaves of the same genetic stocks. Based on these observations, we propose a model in which FLOWERING LOCUS T is up-regulated in the leaves under LDs and is then transported to the shoot apical meristem, where it simultaneously induces the expression of VRN1 and GA biosynthetic genes, which are both required for the up-regulation of the early floral meristem genes SUPPRESSOR OF OVEREXPRESSION OF CONSTANS1-1 and LEAFY and the timely development of the wheat spike.